2018
DOI: 10.1097/ftd.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Once-Daily Tacrolimus Compared With Twice-Daily Tacrolimus in the Early Stage After Living Donor Liver Transplantation

Abstract: The C0 monitoring of the OD formulation may not be optimal in patients at the early stage after LDLT because the C0 was not correlated with the AUC0-24. If clinicians target the same C0 using the OD and TD formulations, the exposure of tacrolimus can be higher in the OD formulation, and excessive immunosuppression should be noted. Particular attention should be paid to the patients in the early stage after LDLT in the use of the OD oral formulation of tacrolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…In addition, a relatively high inter-patient variability of CaN activities was observed. These results are consistent with previous published work on that topic [27][28][29]. We tried to develop a pharmacokinetic-pharmacodynamic model to describe the relationship between TAC exposure and inhibition of its molecular target but all modeling approaches tested failed.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, a relatively high inter-patient variability of CaN activities was observed. These results are consistent with previous published work on that topic [27][28][29]. We tried to develop a pharmacokinetic-pharmacodynamic model to describe the relationship between TAC exposure and inhibition of its molecular target but all modeling approaches tested failed.…”
Section: Plos Onesupporting
confidence: 88%
“…acute cellular rejection [24][25][26]. A few studies, conducted in liver transplantation, described the pharmacokinetic-pharmacodynamic relationship of TAC by studying the link between whole blood concentrations and CaN activity in PBMC [27][28][29]. However, the complete relationship between TAC whole blood concentration, TAC intra-PBMC concentration and TAC-induced CaN inhibition, have only been reported in a preliminary work by our team [30], and remains to be widely explored and emphasized with the drug pharmacogenetics.…”
Section: Plos Onementioning
confidence: 99%
“…3 Monitoring of Cmin is mandatory to minimize the risk of rejection (Cmin below the target range), as well as to reduce the risk of nephrotoxicity, and, to a lesser extent, neurotoxicity (Cmin above the target range). 3,14 In present study, the AUC for twice-daily tacrolimus did not differ significantly from the AUC for once-daily tacrolimus, despite a lower Cmin for the latter. This implies that the same target trough level of tacrolimus cannot be used to predict the efficacy of the drug (AUC) after the conversion, especially among the expressors.…”
Section: Discussioncontrasting
confidence: 57%
“…The safety and efficacy of twice-daily and once-daily tacrolimus in liver transplant recipients were shown to be similar. 3,10,[14][15][16] Several previous studies demonstrated that liver dysfunction is the most common adverse event after converting from twice-daily to once-daily tacrolimus. 11 In our present study, the incidence of liver dysfunction in stable liver transplant recipients converted to once-daily extended-release tacrolimus was higher in the CYP3A5 expressor group than in the non-expressor group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation